Corporate finance : guide to application in banking and fianncial services in Nigeria - Nwoji, Ben I. (Lagos; MalthHouse Press, 1999)
The book is on corporate finance in financial and banking services in Nigeria. It is divided into 12 chapters with a focus on the application of such theories that are relevant to a given situation.
opc 03/01/17
Loans
Keywords: Corporate Finance; Banking and banking; Financial services industry; Nigeria